Study on bonding strength of hot-cast anchors subject to elevated temperature. (December 2022) - Du, Yong; Li, Peng-fang; Huang, Lei
Abstract: Appropriate assessment of the fire resistance of pre-tensioned steel structures depends largely on the ability to reasonably predict anchors response at elevated temperature. The bond strength of hot-cast anchors has been explored at room temperature, whilst that at elevated temperature has been less deeply scrutinised. The aim of this research is to experimentally and numerically investigate the behaviour of hot-cast anchors at elevated temperature. A total of twenty-two sets of hot-cast anchors are prepared for pull-out test at elevated temperature to investigate the ultimate load capacity and failure modes. The tests observe the failure mode including filler fully melted, filler partially melted with bond steel wires slipping and filler slipping with bond steel wires. The three types of failure modes of hot-cast anchors are dependent on the tension force ratio and target heating temperature. A charge-couple device camera (CCDC) system is used to capture the slipping displacement at the end of bonding strands accurately, which experiences linearly slipping, accelerated slipping and jump slipping phase. It takes longer heating time to achieve the critical tension force of hot-cast anchors than jump slipping points. It indicates that filler of hot-cast anchors can provide enough bond strength before jump slipping at elevated temperature. On the basis of examination of all test data, the failure criterion of hot-cast anchors at elevated temperature has been proposed herein that when the slipping displacement of bond steel strands reaches the value of 8.5% of its nominal diameter at elevated temperature, hot-cast anchors would be failed. The transient temperature distribution of hot-cast anchors is investigated by tests, simple method and thermal numerical analysis respectively. A simple method is employed to determine the characteristic temperature of hot-cast anchors as hot-cast anchors fail. Finally, a critical temperature method is generated to check the fire resistance and design fireproof for hot-cast anchors.